The Smc complexes in DNA damage response - Wu, Nan (BioMed Central, 2012)
The structural maintenance of chromosomes (Smc) proteins regulate nearly all aspects of chromosome biology and are critical for genomic stability. In eukaryotes, six Smc proteins form three heterodimers--Smc1/3, Smc2/4, and Smc5/6--which together with non-Smc proteins form cohesin, condensin, and the Smc5/6 complex, respectively. Cohesin is required for proper chromosome segregation. It establishes and maintains sister-chromatid cohesion until all sister chromatids achieve bipolar attachment to the mitotic spindle. Condensin mediates chromosome condensation during mitosis. The Smc5/6 complex has multiple roles in DNA repair. In addition to their major functions in chromosome cohesion and condensation, cohesin and condensin also participate in the cellular DNA damage response. Here we review recent progress on the functions of all three Smc complexes in DNA repair and their cell cycle regulation by posttranslational modifications, such as acetylation, phosphorylation, and sumoylation. An in-depth understanding of the mechanisms by which these complexes promote DNA repair and genomic stability may help us to uncover the molecular basis of genomic instability in human cancers and devise ways that exploit this instability to treat cancers.